2002
DOI: 10.1038/nmat769
|View full text |Cite
|
Sign up to set email alerts
|

High-κ dielectrics for advanced carbon-nanotube transistors and logic gates

Abstract: The integration of materials having a high dielectric constant (high-kappa) into carbon-nanotube transistors promises to push the performance limit for molecular electronics. Here, high-kappa (approximately 25) zirconium oxide thin-films (approximately 8 nm) are formed on top of individual single-walled carbon nanotubes by atomic-layer deposition and used as gate dielectrics for nanotube field-effect transistors. The p-type transistors exhibit subthreshold swings of S approximately 70 mV per decade, approachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
723
3
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 928 publications
(757 citation statements)
references
References 35 publications
14
723
3
2
Order By: Relevance
“…In the case of the SWCNT FET in Figure 3a, the DIBL is ∆V th /∆V DS ) 700 mV/V, which is similar to previously reported carbon nanotube FETs with similar channel length. 9,13 Theoretical work has shown that DIBL in short-channel SWCNT FETs can be reduced by implementing a double-gate, triple-gate, or surround-gate device structure. 17 Combining patterned bottom gate electrodes 12 with a thin, SAM-based gate dielectric 16 offers a number of advantages.…”
mentioning
confidence: 99%
“…In the case of the SWCNT FET in Figure 3a, the DIBL is ∆V th /∆V DS ) 700 mV/V, which is similar to previously reported carbon nanotube FETs with similar channel length. 9,13 Theoretical work has shown that DIBL in short-channel SWCNT FETs can be reduced by implementing a double-gate, triple-gate, or surround-gate device structure. 17 Combining patterned bottom gate electrodes 12 with a thin, SAM-based gate dielectric 16 offers a number of advantages.…”
mentioning
confidence: 99%
“…19 The position of the Fermi level is measured by the threshold voltage, and an extensive literature has established the relationship between the threshold voltage in various device configurations and the quantity of charge induced in the nanotubes. [20][21][22] In our case, with a typical nanotube diameter of 2 nm, every 1 µm of nanotube length has a capacitance to the gate, C bg , of 15 aF. 20 The induced charge, ∆Q, is given by ∆Q ) C bg ∆V, where ∆V is the threshold shift.…”
mentioning
confidence: 99%
“…While multiwalled CNTs (MWNTs) show complicated electrical properties, single-walled CNTs (SWNTs) are either metallic or semiconducting depending on the atomic structure [3,4]. Utilizing such electrical properties, SWNTs have been applied to demonstrate single device performance including field-effect transistor [5], random access memory [6], room-temperature single-electron transistor [7], and logic gates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%